2023
DOI: 10.3390/children10091530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Movement and Storytelling Intervention on Fundamental Motor Skills, Language Development and Physical Activity Level in Children Aged 3 to 6 Years: Study Protocol for a Randomized Controlled Trial

Rodrigo Vargas-Vitoria,
César Faúndez-Casanova,
Alberto Cruz-Flores
et al.

Abstract: This study protocol aims to analyze and compare the effects of combined movement and storytelling intervention (CMSI) on fundamental motor skills (locomotor skills and object control), language development (language comprehension, language expression, vocabulary and language description), and physical activity levels (light intensity, moderate-to-vigorous intensity and sedentary time) in children aged 3 to 6 years. The sample will consist of 144 children from 12 class groups, randomly assigned to 3 experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Lately, few studies have designed protocols and examined the effectiveness of combined movement and storytelling interventions in motor, cognitive, and/or linguistic skills in preschool children [25][26][27][28]. More specifically, Duncan et al [25] reported that a 6-week (2 times/week; 30 min/time) combined movement and storytelling intervention program, in kindergarten, enhanced motor competence and language ability in preschool children to a greater extent than movement or storytelling alone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lately, few studies have designed protocols and examined the effectiveness of combined movement and storytelling interventions in motor, cognitive, and/or linguistic skills in preschool children [25][26][27][28]. More specifically, Duncan et al [25] reported that a 6-week (2 times/week; 30 min/time) combined movement and storytelling intervention program, in kindergarten, enhanced motor competence and language ability in preschool children to a greater extent than movement or storytelling alone.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Eyre et al [26] found that a 12-week combined movement and storytelling intervention program (1 time/week; 35 min/time), in kindergarten, significantly improved different motor skills in both White and South Asian preschool children. More recently, Vargas-Vitoria et al [28] developed and designed a 12-week (3 times/week; 40 min/time) combined movement and storytelling intervention program for preschool children. The effectiveness of the above program on fundamental motor skills, language development, and physical activity level is expected to be examined by the authors in Chilean children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation